Bailout : an insider's account of bank failures and rescues - Sprague, Irvine H. (Washington : BeardBooks, 2000)
This book contains all the major bank crises since the Great Depression. He describes the reasons for the actions taken and the options he considers to have been available to the FDIC and other regulatory agencies. The book makes for fascinating reading that highlights the problems and concerns for public policy toward banking. It represents 'must' reading for all students of banking
Originally published: New York : Basic Books, c1986.
Includes bibliographical references and index.
gau 16/06/14
Loans
Keywords: Deposit insurance; Bank failures; Federal deposit insurance corporation; United States